IMPLEMENTASI BLENDED LEARNING MELALUI APLIKASI WHATSAPP DALAM MENINGKATKAN LISTENING SISWA DI SMA NEGERI 2 LHOKSEUMAWE - Rahmati Rahmati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aims to determine the listening skills of class XII students at SMA Neg. 2 Lhokseumawe Academic Year 2022/2023 through the implementation of Blended Learning using the WhatsApp application as a media. This research is a classroom action research (CAR) This research consisted of one cycle that consisted of four steps, they are: planning, action, observation, and reflection. To collect data, researchers carried out three steps, namely: Pre-test, Treatment, and Post-test. To analyze the data, researchers used a quantitative research design. Quantitative data were obtained from the pre-test and post-test scores of class XII students. The results showed that there was a significant increase in students' listening skills through the application of the Blended Learning model using the WhatsApp application. The increase can be seen from the pre-test and post-test values in one cycle. In the pre-test, the main score is 60.95 and in the post-test, the main score is 90.55. The average value of the post-test is higher than the pre-test, with an increase of 48.56%. Based on the findings, it can be concluded that the implementation of Blended Learning through the WhatsApp application can improve students' listening skills